2010
DOI: 10.1161/circulationaha.109.925396
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Fractional Flow Reserve–Guided Percutaneous Coronary Intervention in Patients With Multivessel Disease

Abstract: Background-The Fractional Flow Reserve Versus Angiography for Multivessel Evaluation (FAME) study demonstrated significantly improved health outcomes at 1 year in patients randomized to multivessel percutaneous coronary intervention guided by fractional flow reserve (FFR) compared with percutaneous coronary intervention guided by angiography alone. The economic impact of routine measurement of FFR in this setting is not known. Methods and Results-In this study, 1005 patients were randomly assigned to FFR-guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
194
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 334 publications
(208 citation statements)
references
References 21 publications
10
194
0
4
Order By: Relevance
“…An economic evaluation verified that FFR-guided PCI is a cost-saving strategy 13 , with fewer stents deployed and less contrast used. FIND study had showed that FFR is cost effective.…”
mentioning
confidence: 85%
“…An economic evaluation verified that FFR-guided PCI is a cost-saving strategy 13 , with fewer stents deployed and less contrast used. FIND study had showed that FFR is cost effective.…”
mentioning
confidence: 85%
“…A recent study with an assessment of fractional flow reserves also showed that CAG is not always accurate for assessing the functional significance of a coronary stenosis, regardless of the angiographic severity (3). Unnecessary revascularization can lead to increased costs, radiation exposure, and procedural complications without clinical benefits (4,5). In our present study, the CAG group underwent more coronary revascularization.…”
Section: Discussionmentioning
confidence: 55%
“…However, substantial discrepancies between angiographic anatomic findings and functional severity of stenosis have been noted (2,3). Additionally, coronary revascularization without documentation of ischemia using functional tests might lead to increased medical costs and deterioration in clinical prognoses (4)(5)(6).…”
mentioning
confidence: 99%
“…42 In the FFR group, the number of stents per patient (1.9±1.3 vs 2.7±1.2) and the primary end point of death, non-fatal myocardial infarction or target vessel revascularisation at 1 year (13.2% vs 18.3%) were both significantly lower than for the angiography group. Benefits were largely sustained at 2 years 43 and evidence of cost-effectiveness 44 completes the case in favour of FFR-guided PCI in multivessel procedures.…”
Section: Pressure Wirementioning
confidence: 84%